Enhancing intestinal barrier efficiency: A novel metabolic diseases therapy - Zhang, Yaoyuan; Zhu, Xiao; Yu, Xinyuan; Novák, Petr; Gui, Qingjun; Yin, Kai (Frontiers in Nutrition, 2023)
Physiologically, the intestinal barrier plays a crucial role in homeostasis and nutrient absorption and prevents pathogenic entry, harmful metabolites, and endotoxin absorption. Recent advances have highlighted the association between severely damaged intestinal barriers and diabetes, obesity, fatty liver, and cardiovascular diseases. Evidence indicates that an abated intestinal barrier leads to endotoxemia associated with systemic inflammation, insulin resistance, diabetes, and lipid accumulation, accelerating obesity and fatty liver diseases. Nonetheless, the specific mechanism of intestinal barrier damage and the effective improvement of the intestinal barrier remain to be explored. Here, we discuss the crosstalk between changes in the intestinal barrier and metabolic disease. This paper also highlights how to improve the gut barrier from the perspective of natural medicine, gut microbiota remodelling, lifestyle interventions, and bariatric surgery. Finally, potential challenges and prospects for the regulation of the gut barrier-metabolic disease axis are discussed, which may provide theoretical guidance for the treatment of metabolic diseases.